Numerical Study of the Hydrodynamic Performance of a Two-Propeller Configuration - Xunming Wang; Yongyan Ma; Dakui Feng; Chaobang Yao; Zichao Cai (Journal of Marine Science and Engineering)
Improved ship design and market demands have driven the adoption of multi-propeller systems for propulsion in recent years. This study examines the hydrodynamic performance of two KP505 propellers arranged in various transverse and longitudinal spacings, utilizing an in-house CFD code. The numerical simulations employ the URANS method with the SST k-ω turbulence model and a structured overset grid approach. First, standardized mesh and time-step convergence studies are conducted following ITTC recommendations. The hydrodynamic results for the KP505 propeller are compared with experimental data to validate the reliability of the method. Subsequently, over 40 propeller arrangements with varying transverse and longitudinal spacing are simulated. Thrust, torque, and efficiency under different operating conditions are calculated, and key flow field data are analyzed. Finally, the interference characteristics between propellers at different positions are examined by comparing the results with those of a single KP505 propeller. The findings indicate that the high-speed wake generated by the upstream propeller significantly affects the hydrodynamic performance of the downstream propeller. This interaction diminishes as the transverse spacing between the propellers increases. To ensure the propulsion efficiency of the two-propeller configuration, the transverse spacing should not be less than one times the diameter of the propeller.